Abstract Fractional Monotone Approximation, Theory and Applications - Anastassiou, George A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book employs an abstract kernel fractional calculus with applications to Prabhakar and non-singular kernel fractional calculi. The results are univariate and bivariate. In the univariate case, abstract fractional monotone approximation by polynomials and splines is presented. In the bivariate case, the abstract fractional monotone constrained approximation by bivariate pseudo-polynomials and polynomials is given. This book$1 (Bs results are expected to find applications in many areas of pure and applied mathematics, especially in fractional approximation and fractional differential equations. Other interesting applications are applied in sciences like geophysics, physics, chemistry, economics, and engineering. This book is appropriate for researchers, graduate students, practitioners, and seminars of the above disciplines.s
Basic abstract fractional monotone approximation -- Abstract bivariate left fractional monotone constrained approximation by pseudo-polynomials -- Conclusion.
Keywords: Engineering mathematics; Control engineering; Engineering$1 (BData processing.s; Engineering Mathematics; Control and Systems Theory; Mathematical and Computational Engineering Applications; Fractional calculus